Bread Dough Mixer Design with Safe Structural Performance: Desain Mesin Pengaduk Adonan Roti dengan Kinerja Struktur yang Aman - Arif Rachmandani; Mulyadi (Indonesian Journal of Innovation Studies, 2025)
General Background: Bread dough mixing equipment is an essential component in food production processes and is required to support efficient and practical operations in small-scale and home industries. Specific Background: Many bread producers still rely on manual mixing methods, creating a need for machine-based solutions capable of processing dough with appropriate capacity and structural reliability. Knowledge Gap: Limited information is available regarding the conceptual design and structural simulation of a bread dough mixer specifically developed for a 3 kg dough capacity using a systematic design approach. Aims: This study aimed to develop a bread dough mixer design with a 3 kg dough capacity and evaluate the structural performance of its frame through static loading simulation. Results: Using the morphological chart method, two design concepts were generated and Concept B was selected for further development. The designed system employed a 0.5 HP AC motor and a bowl capacity of 14.7 liters. Static simulations under loads of 170 N, 200 N, and 370 N showed that the highest load produced a maximum von Mises stress of 5.97 MPa, maximum displacement of 0.02459 mm, maximum strain of 1.97 × 10⁻⁵, and a minimum safety factor of 41.9. Novelty: The study presents a structured combination of morphological concept selection, mechanical component planning, and numerical structural assessment for a 3 kg bread dough mixer design. Implications: The findings indicate that the proposed design fulfills structural safety requirements and provides a feasible reference for future realization of bread dough mixing equipment for home industry applications.Highlights: Concept B was selected through systematic concept evaluation and proceeded to detailed development. The planned machine utilized a 0.5 HP AC motor and a 14.7-liter mixing container. Structural assessment under 370 N loading produced a minimum safety factor of 41.9, indicating secure frame conditions. Keywords: Bread Dough Mixer; Mechanical Design; Morphological Chart; Static Load Simulation; Structural Safety